Restorative campus landscapes: fostering education through restoration - Gutierrez, Josef (Kansas State University, 2013)
Restorative landscapes are a growing trend within health care environments and can have a lasting impact on people if applied within other settings, particularly higher education campuses. Their design captures the many healing qualities of nature that humans are instinctively attracted to (Heerwagen, 2011). Within restorative landscapes, people have been historically found to experience relief of stress, improved morale, and improved overall well-being (Barnes et al., 1999). While campus planning standards do consider the outdoor environment as an extension of the classroom, higher education campuses can do more to utilize the cognitive benefits of nature for students, faculty and staff. This project explores principles and theories of restorative landscape design, empirical psychological research, and campus design to develop a framework that facilitates the creation of restorative campus spaces on higher education campuses. In partnership with the Office of Design and Construction Management at the University of Kansas, the framework was subsequently applied through the design of the landscape for the Center for Design Research on the KU campus. In the context of current campus planning challenges, restorative landscape design is a potentially valuable strategy in strengthening the beneficial roles and efficacy of the campus landscape. This design project explores its application to envision places within a higher education campus that, along with other benefits, relieve stress for students, faculty and staff.
Keywords: Restorative Landscapes; Therapeutic Landscapes; Healing Gardens; Campus Design; Campus Planning; University of Kansas; Landscape Architecture (0390)